Nitric oxide promotes adventitious root formation in cucumber under cadmium stress through improving antioxidant system, regulating glycolysis pathway and polyamine homeostasis - Niu, Lijuan; Tang, Yunlai; Zhu, Bo; Huang, Zhenfu; Wang, Dan; Chen, Qiyang; Yu, Jian (Frontiers in Plant Science, 2023)
Cadmium (Cd) as a potentially toxic heavy metal that not only pollutes the environment but also interferes with plant growth. Nitric oxide (NO) regulates plant growth and development as well as abiotic stress response. However, the mechanism underpinning NO-induced adventitious root development under Cd stress remains unclear. In this study, cucumber (Cucumis sativus ‘Xinchun No. 4’) was used as the experimental material to investigate the effect of NO on the development of adventitious roots in cucumber under Cd stress. Our results revealed that, as compared to Cd stress, 10 μM SNP (a NO donor) could considerably increase the number and length of adventitious roots by 127.9% and 289.3%, respectively. Simultaneously, exogenous SNP significantly increased the level of endogenous NO in cucumber explants under Cd stress. Our results revealed that supplementation of Cd with SNP significantly increased endogenous NO content by 65.6% compared with Cd treatment at 48 h. Furthermore, our study indicated that SNP treatment could improve the antioxidant capacity of cucumber explants under Cd stress by up-regulating the gene expression level of antioxidant enzymes, as well as reducing the levels of malondialdehyde (MDA), hydrogen peroxide (H2O2) and superoxide anion (O2 ·-) to alleviate oxidative damage and membrane lipid peroxidation. Application of NO resulted in a decrease of the O2·-, MDA, and H2O2 level by 39.6%, 31.4% and 60.8% as compared to Cd-alone treatment, respectively. Besides that, SNP treatment significantly increased the expression level of related genes involved in glycolysis processes and polyamine homeostasis. However, application of NO scavenger 2-(4-carboxy -2-phenyl)-4, 4, 5, 5-tetramethy limidazoline -1-oxyl -3-oxide (cPTIO) and the inhibitor tungstate significantly reversed the positive role of NO in promoting the adventitious root formation under Cd stress. These results suggest that exogenous NO can increase the level of endogenous NO, improve antioxidation ability, promote glycolysis pathway and polyamine homeostasis to enhance the occurrence of adventitious roots in cucumber under Cd stress. In summary, NO can effectively alleviate the damage of Cd stress and significantly promote the development of adventitious root of cucumber under Cd stress.